Myślenie artystyczne i myślenie mityczne = Artistic and mythical thinking - Sapeńko, Roman (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author attempts to show similarities and differences between artistic and mythical perceptions of the world. Analysing the transformation of mythical thinking into artistic thinking, the article shows the role of the conceptual metaphor mechanism in this process.
Keywords: myślenie artystyczne; myślenie mityczne; metafory pojęciowe; teoria; artistic thinking; mythical thinking; conceptual metaphors; literacy theory